Public participation approaches in shaping Colombian food policies - Conejero, Elena García; Nilgen, Marco (Citizens Juries Colombia, 2023)
While our planned research in Colombia aims to contribute to a more thorough understanding of the dynamics within citizens’ juries, a key component at the foundation of our project is, of course, to understand the country’s history of implementing bottom-up public participation processes, particularly in the context of food-system policies. In the wake of constitutional reforms, and the ongoing decentralization journey that Colombia has embarked on in 1991, the landscape of public engagement in food-system-related policies has witnessed a significant evolution. While the country’s constitutional framework provides fundamental mechanisms that offer citizens direct involvement in electing national, regional, and local representatives, the scope of public participation extends beyond the ballot box, encompassing community-driven processes where citizens identify needs, formulate projects, and actively engage in improving their living conditions. Accordingly, recent developments have witnessed a surge in innovative strategies of citizenry engagement that range from the utilization of popular initiatives and referendums to community assemblies and participatory policy formulations. Through a synthesis of academic literature and contemporary case studies, this blogpost provides a brief overview of public participation strategies in the realm of Colombian food system policies that have emerged in recent years, while helping readers understand how citizen contribution has become a cornerstone in shaping inclusive, responsive, and contextually relevant food policies.